2019
DOI: 10.1007/s13361-019-02177-8
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Phase Collisions with Trimethylamine-N-Oxide Enable Activation-Controlled Protein Ion Charge Reduction

Abstract: Modulating protein ion charge is a useful tool for the study of protein folding and interactions by electrospray ionization mass spectrometry. Here, we investigate activation-dependent charge reduction of protein ions with the chemical chaperone trimethylamine- N -oxide (TMAO). Based on experiments carried out on proteins ranging from 4.5 to 35 kDa, we find that when combined with collisional activation, TMAO removes approximately 60% of the charges acquired under native conditions. Ion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 18 publications
3
24
0
Order By: Relevance
“…To elucidate the mechanism of charge reduction by alkali metals in ELIC, we analyzed the effect of other charge-reducing agents, including triethylamine (TEA), imidazole, and trimethylamine N -oxide (TMAO). ,,, Additionally, we examined the possibility that charge reduction is occurring through a specific interaction with the protein by comparing the aforementioned charge-reducing agents with the effect of a known agonist of ELIC, cysteamine . Imidazole, TEA, TMAO, and cysteamine were separately introduced, and the respective samples were analyzed by native MS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To elucidate the mechanism of charge reduction by alkali metals in ELIC, we analyzed the effect of other charge-reducing agents, including triethylamine (TEA), imidazole, and trimethylamine N -oxide (TMAO). ,,, Additionally, we examined the possibility that charge reduction is occurring through a specific interaction with the protein by comparing the aforementioned charge-reducing agents with the effect of a known agonist of ELIC, cysteamine . Imidazole, TEA, TMAO, and cysteamine were separately introduced, and the respective samples were analyzed by native MS.…”
Section: Resultsmentioning
confidence: 99%
“…Altering the detergent to polyethylene glycol (PEG)-based or amine N -oxide amphiphiles affords meaningful charge reduction; even so, the degree of charge reduction may be insufficient to prevent the deleterious effects of excessive Coulombic repulsion . To further reduce charge, small molecules are added to the protein solution including triethylamine (TEA), imidazole, and trimethylamine N -oxide (TMAO). ,,, Recently, Townsend et al reported a new host of imidazole analogues that aid in charge reduction and afford peptide–nanodisc stability . However, these small amine-containing molecules may interact with the protein and result in undesired effects.…”
mentioning
confidence: 99%
“…The most commonly used method is to add charge reducing reagents to solution prior to ESI. Imidazole and triethylamine (TEA) are commonly used, but recent work has shown that trimethylamine oxide (TMAO) can be a potent charge reducing reagent. However, TMAO tends to form adducts with protein complexes, which is an important component of its activity …”
mentioning
confidence: 99%
“…Trimethylamine- N -oxide (TMAO) is a basic osmolyte that strips protons off ionized proteins through collisions in the gas phase. 41 , 42 After addition of 50 mM TMAO to the ESI solution, both proteins shift to lower charge states ( Figure S3 ). However, we also observed that the intensity of the EXG QQQW peaks was significantly reduced.…”
Section: Resultsmentioning
confidence: 99%